Politics and culture in Renaissance Naples - Bentley, Jerry H., 1949-2012 (Princeton legacy library, 1987)
Examining the cultural history of Renaissance Naples with an emphasis on humanism, the author also evaluates Naples in the broader context of fifteenth-century Italy and Renaissance Europe in general. He addresses several prominent themes of Renaissance history: patron- client relationships, the development of a realistic, Machiavellian approach to matters of statecraft and diplomacy, and the influence of Neapolitan humanists on European culture in general. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.